Analysis of Inductance Gradient and Current Density Distribution Over Different Cross-section of Rails - M. N. Saravana Kumar; R. Murugan (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In a rail gun system the armature accelerated due to the Lorentz force caused by the current which is diffused in to the rails. The entire system depends on the inductance gradient of the rail which is directly connected to the accelerating performance and efficiency of railgun. Hence, the exact analysis of inductance gradient is extremely significant for the railgun design. Since short duration of current pulse is applied to the rails determination of inductance gradient is very difficult. The inductance gradient varies with the geometric dimensions of the rails and armature. And it can be calculated with analytical method and numerical methods. In this paper inductance gradient of the rail has been computed and compared with the different rail cross-sectional models using Ansoft Maxwell Eddy current solver uses finite element technique to calculate the field distribution in a space. The current density, magnetic flux density, repulsive force acting on the rails also computed to analyze the performance of rail gun.